En koncessionsløs tekst. Fjodor Dostojevskijs "Idioten" læst som anti- og procesroman - Andersen, Jørn Erslev (Passage - Tidsskrift for litteratur og kritik, 2013)
Jørn Erslev Andersen: “A Text without Concession: Fyodor Dostoyevsky’s The Idiot Read as Anti- and Process Novel” The vast amount of conflicting narrative and stylistic features in Dostoyesky’s novel The Idiot is a well-known fact. The article proposes a reading of the novel dealing with these conflicting features in the perspectives of the anti- and process novel. The concept of the anti-novel serves as a new reading perspective and is exemplified through comparative comments on The Idiot and Flaubert’s Madame Bovary, and on Don Quixote and Prince Myshkin. The concept of the process novel is created by among others Catteau and Morson. The reading proposes yet another dimension of this concept by commenting on Holbein’s Erasmian Art and its presence in and understanding of the portrait of Prince Myshkin. The article concludes by understanding both the novel itself and its protagonist as actual entities.